Odpowiedzi

Najlepsza Odpowiedź!
2009-12-27T15:59:40+01:00
3x-2y=11 ==> x=(11+2y):3
4x-5y=3
podstawiam x do drugiego równania:
4(11+2y):3-5y=3
(44+8y):3-5y-3=0 |*3
44+8y-15y-9=0
-7y+35=0
7y=35
y=5

x=(11+2*5):3
x=21:3
x=7

odp x=7, y=5
2009-12-27T16:00:42+01:00
3x-2y=11
4x-5y=3

3x=11+2y |:3
4x-5y=3

x=3⅔+⅔y
4(3⅔+⅔y)-5y=3

x=3⅔+⅔y
14⅔+2⅔y-5y=3

x=3⅔+⅔y
14⅔-2⅓y=3

x=3⅔+⅔y
-2⅓y=3-14⅔

x=3⅔+⅔y
-2⅓y=-11⅔ |:-2⅓

x=3⅔+⅔y
y=5

x=3⅔+3⅓
x=7
2009-12-27T16:54:59+01:00
3x-2y=11
4x-5y=3

3x=11+2y |:3
4x-5y=3

x=3⅔+⅔y
4(3⅔+⅔y)-5y=3

x=3⅔+⅔y
14⅔+2⅔y-5y=3

x=3⅔+⅔y
14⅔-2⅓y=3

x=3⅔+⅔y
-2⅓y=3-14⅔

x=3⅔+⅔y
-2⅓y=-11⅔ |:-2⅓

x=3⅔+⅔y
y=5

x=3⅔+3⅓
y=5

x=7
y=5